2021
DOI: 10.1186/s40359-020-00509-y
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety among dental professionals and its association with their dependency on social media for health information: insights from the COVID-19 pandemic

Abstract: Background Social media can play a detrimental role during a global health emergency. In this study, we aimed at assessing the impact social media has on the anxiety level of dental healthcare workers (DHCWs) whilst living through the COVID-19 pandemic. Methods An online questionnaire was disseminated to a cross-sectional sample of DHCWs from 19 countries using social media platforms. The questionnaire enquired about DHCWs’ frequency of using socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
2
17
1
1
Order By: Relevance
“…Females reported a higher level of stress (bivariate analysis); this finding is similar to those of studies involving dental staff [19], although another study did not report differences between males and females [15]. Some studies focused on other mental health indicators have exhibited gender differences-for example, a study with a cross-sectional sample of DHCWs from 19 countries using social media platforms reported higher anxiety in females [20]. The same situation was found in the case of studies carried out in Ecuador [27] and Turkey [22].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Females reported a higher level of stress (bivariate analysis); this finding is similar to those of studies involving dental staff [19], although another study did not report differences between males and females [15]. Some studies focused on other mental health indicators have exhibited gender differences-for example, a study with a cross-sectional sample of DHCWs from 19 countries using social media platforms reported higher anxiety in females [20]. The same situation was found in the case of studies carried out in Ecuador [27] and Turkey [22].…”
Section: Discussionsupporting
confidence: 74%
“…In this sense, the impact of social media on the mental health of dental staff should be considered. A cross-sectional study conducted in DHCWs from 19 countries showed that the social media infodemic has affected the psychological well-being of dental students and dentists since a statistically significant association was found between the presence of anxiety and the frequency of use of social media [20]. However, we found variables associated in the bivariate analyses (statistically significant) with the stress perceived by the study's participants and that are related to knowledge and attitudes related to COVID-19.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Even though online presence and social media are portrayed as key factors for dental clinics' growth [33,34], there are many issues and challenging edges that these types of businesses are facing nowadays [35,36]. For example, social media has become an integral part of patients' lives [37,38], and this fact stimulates professionals to align their promotional actions to the highly requested need for personalization. The challenging necessity of delivering a good experience and building trust and long-term relationships [39][40][41] represents "'the most important way to attract and convert new patients into lifelong ones" who will choose to remain faithful to a clinic [42].…”
Section: Introductionmentioning
confidence: 99%